Gender roles in the Anchovies Food Supply Chain – Bagang System in Mempakad Laut, North Borneo, Malaysia - Jurry Foo @ Jurry F. Michael; Diana Demiyah Mohd Hamdan; Sharifah Rahama Amirul; Siti Muslihah Sapari; Nur Hazirah Janoni; Emily Jotin (Institution for Marine and Island Cultures, Mokpo National University, 2022)
This article examines the roles of gender in the Bagang system, an organisation of the anchovy supply chain in Mempakad Laut, Sabah, Malaysia bordering the Marine Protected Area named Tun Mustapha Marine Park. Gender study on marine ecosystem management is important to understand the involvement of men and women specifically on how they are complementing each other in ensuring effective resource management. This exploratory study was obtained via qualitative approach as the data collections method including Focus Group Discussion (FGD), interviews as well as field observation. A total of 30 informants participated in this study which were selected through purposive sampling and snowball sampling method. Findings reveal that men and women are equally important in the Bagang system. Men work on marine affairs and material development, while women work on product processing and marketing. The contribution of women in the sustainability of the Bagang system was significantly visible and was treated equally in most aspects notably in financial management and in the decision-makings from the initial to the end of the anchovy supply chain. These findings are very important as guidelines to plan a better sustainable marine management for the future and a fine example of how sustainable fisheries can be achieved in supporting the United Nations Sustainable Development Goals No. 5 which is gender equality.